Participatory research with co-researchers with lived experience of psychosis high risk states - Hinterbuchinger, Barbara; Kaisler, Raphaela E.; Baumgartner, Josef S.; Friedrich, Fabian; Litvan, Zsuzsa; Trimmel, Melanie; Hlavacek, Karin; Popa, Alina Ramya; Mossaheb, Nilufar, The VOICE Consortium (Frontiers in Psychiatry, 2025)
BackgroundAlthough in psychiatric research prevention and participation are both considered increasingly important, there are few participatory research projects with individuals with psychosis high risk states (ultra-high risk for psychosis; UHR). The aim of this project was to reflect on UHR terminology, diagnostic and treatment guidelines and to identify and implement unmet needs together with people at UHR.MethodsThis project was designed co-creatively from the conceptual phase to the execution. The project team consisted of an equal number of mental health clinicians and co-researchers with lived UHR experience. Rules for collaboration were co-creatively developed within the group. Within 4 project workshops, project objectives and unmet needs were identified and prioritized. After setting up an action plan, project plans were implemented within the research group.ResultsUnmet needs of co-researchers with lived UHR-experience included free access to information on psychosis high risk states, opportunities for personal exchange, and the creation of more public awareness and knowledge about UHR. Within the participatory research process, consensus on collaboration and objectives was achieved and heterogeneous perceptions towards the UHR concept and terminology were discussed.ConsensusThe necessity of an adequate terminology for psychiatric conditions was deemed crucial by both medical professionals and co-researchers with lived UHR experience for facilitating a better understanding between psychiatrists and those affected. Heterogeneity of perception illustrates the necessity of addressing individual needs and utilising diverse terminology and explanatory models within mental health.